Laparoscopy‐assisted vasovasostomy for post‐herniorrhaphy vas deferens obstruction. Issue 2 (24th February 2020) - Uchida, Masahiro; Iida, Shuichi; Hoshi, Kazuhiko; Kojo, Kosuke; Tsuchiya, Haruki; Yamasaki, Kazumitsu; Miyazaki, Jun; Iwamoto, Teruaki
Abstract : Introduction: Repair of obstructive azoospermia caused by childhood herniorrhaphy may be difficult. Therefore, intracytoplasmic sperm injection using testicular sperm is performed. However, vasovasostomy combined with laparoscopic surgery is challenging. Case presentation: A 42‐year‐old man underwent inguinal hernia repair at age 3. He had normal testicular size, azoospermia, normal hormone levels (follicle‐stimulating hormone, luteinizing hormone, and testosterone), absence of Y chromosome micro deletion, and karyotype:46XY, t(1:21)(p34.1:q22.3). He was diagnosed with obstructive azoospermia. Repeated intracytoplasmic sperm injections using testicular sperm resulted in miscarriages. Vasovasostomy combined with laparoscopic surgery was subsequently performed. Postoperative semen analysis result was almost normal. After intracytoplasmic sperm injection of ejaculated sperm, his wife got pregnant. Conclusion: Even if patients have chromosomal abnormalities, performing microsurgical re‐anastomosis first is recommended. To our knowledge, this is the first case of a laparoscopy‐assisted vasovasostomy for post‐herniorrhaphy vas deferens obstruction in Japan.